2019
DOI: 10.1136/emermed-2018-208153
|View full text |Cite
|
Sign up to set email alerts
|

Adapting the Canadian CT head rule age criteria for mild traumatic brain injury

Abstract: ObjectiveWith the ageing population, the prevalence of mild traumatic brain injury (mTBI) among older patients is increasing, and the age criteria of the Canadian CT head rule (CCHR) is challenged by many emergency physicians. We modified the age criteria of the CCHR to evaluate its predictive capacity.MethodsWe conducted a retrospective cohort study at a level 1 trauma centre ED of all mTBI patients 65 years old and over with an mTBI between 2010 and 2014. Main outcome was a clinically important brain injury … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 7 publications
1
8
0
Order By: Relevance
“…Unlike the previous study conducted in Canada, a modified version of the CCHR with a cut-off age of 75 years retained 100% sensitivity but increased specificity to 13.9%. [9] This can be explained by the fact that in older patients, physicians often cannot obtain an accurate history of the accident, and the mechanism of head injury in the elderly is typically low, with a rare loss of consciousness. Additionally, all previous studies were conducted in Western populations, while our study focused on Asians.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike the previous study conducted in Canada, a modified version of the CCHR with a cut-off age of 75 years retained 100% sensitivity but increased specificity to 13.9%. [9] This can be explained by the fact that in older patients, physicians often cannot obtain an accurate history of the accident, and the mechanism of head injury in the elderly is typically low, with a rare loss of consciousness. Additionally, all previous studies were conducted in Western populations, while our study focused on Asians.…”
Section: Discussionmentioning
confidence: 99%
“…[8] A small study in Canada found that using a cut-off age of 75 years in the CCHR criteria increases specificity while maintaining 100% sensitivity. [9] Therefore, the current cut-off age of 65 years may not be appropriate for this population in terms of screening for TBI.…”
mentioning
confidence: 97%
“…Many clinicians continue to interpret the rule as suggesting that all patients aged > 65 require a CTB after a head strike without considering whether it was appropriate to apply the rule in the first place. In a retrospective cohort study, Fournier at al [17]. demonstrated that increasing the high-risk age criteria from 65 years to 75 years was associated with an increase in the Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Due to this Fournier et al suggest increasing the age limit from 65 to 75 years-old. The fact of adjusting the age limit to 75 yearold in the Canadian head CT rule may reduce head CTscans performed of 25% without any intracranial lesion missed [27]. In their retrospective cohort, Riccardi et al even suggested to increase this limit to 80 years old [9].…”
Section: Discussionmentioning
confidence: 99%